Health studies: opportunities for the development of Human Biomonitoring in Europe - Namorado, Sónia (2020)
Introduction: Human Biomonitoring (HBM) and health studies are very similar in terms of the infrastructure and procedures necessary for their implementation, as in either type of studies data is collected through fieldwork, which constitutes one of the largest expenditures for such studies. Thus, combined studies could result in more cost-effective ways to conduct health and environmental monitoring. As such, within the HBM4EU project an inventory of the health studies available which could include an HBM component was performed. Methods: An online questionnaire was developed to collect information on recently conducted, ongoing and planned health studies, which could be linked to an HBM study. The link to the questionnaire was distributed with the help of the National Hub Contact Points of the HBM4EU project. Results: From the 58 different studies included in this inventory, half were longitudinal and presented the possibility of introducing an HBM component in the future. Most of the studies for which data was reported had public funding, either from the government or from public grants (national or European). The vast majority of the studies included the collection of biological samples and the most frequently stored samples were blood, plasma, serum or DNA. More than 50% of the studies reported that the measurement of chemicals was already performed or was planned to be performed. The most frequently measured chemicals were phthalates, bisphenols and cadmium. Conclusions: In vast majority of the studies included in the inventory biological samples are collected and stored, posing the opportunity to use them in HBM studies for the analyses of chemicals of interest. About 50% of these studies already had ethical approval to measure chemicals from collected samples. Funding: HBM4EU has received funding from the European Union’s Horizon 2020 research and innovation programme (grant agreement 733032).